Enterprise content and search management for building digital platforms - Shivakumar, Shailesh Kumar (Wiley, 2016)
"Provides modern enterprises with the tools to create a robust digital platform utilizing proven best practices, practical models, and time-tested techniques Contemporary business organizations can either embrace the digital revolution & mdash;or be left behind. Enterprise Content and Search Management for Building Digital Platforms provides modern enterprises with the necessary tools to create a robust digital platform utilizing proven best practices, practical models, and time-tested techniques to compete in the today & rsquo;s digital world. Features include comprehensive discussions on content strategy, content key performance indicators (KPIs), mobile-first strategy, content assessment models, various practical techniques and methodologies successfully used in real-world digital programs, relevant case studies, and more.-